Circular bioeconomy in African food systems: what is the status quo? Insights from Rwanda, DRC, and Ethiopia - Sekabira, H.; Nijman, E.; Spath, L.; Krutli, P.; Schut, M.; Vanlauwe, Bernard; Wilde, B.; Kintche, K.; Kantengwa, S.; Feyso, A.; Kigangu, B.; Six, Johan (2022)
Increasing global food insecurity amidst a growing population and diminishing production resources renders the currently dominant linear production model insufficient to combat such challenges. Hence, a circular bioeconomy (CBE) model that ensures more conservative use of resources has become essential. Specifically, a CBE model that focuses on recycling and reusing organic waste is essential to close nutrient loops and establish more resilient rural-urban nexus food systems. However, the CBE status quo in many African food systems is not established. Moreover, scientific evidence on CBE in Africa is almost inexistent, thus limiting policy guidance to achieving circular food systems. Using a sample of about 2,100 farmers and consumers from key food value chains (cassava in Rwanda, coffee in DRC, and bananas in Ethiopia), we explored existing CBE practices; awareness, knowledge, and support for CBE practices; consumers’ opinions on eating foods grown on processed organic waste (CBE fertilizers), and determinants of such opinions. We analysed data in Stata, first descriptively, and then econometrically using the ordered logistic regression, whose proportional odds assumption was violated, thus resorting to the generalized ordered logistic regression. Results show that communities practice aspects of CBE, mainly composting, and are broadly aware, knowledgeable, supportive of CBE practices, and would broadly accept eating foods grown CBE fertilizers. Households with heads that used mobile phones, or whose heads were older, or married, or had a better education and agricultural incomes were more likely to strongly agree that they were knowledgeable and supportive of CBE practices and would eat CBE foods (foods grown on processed organic waste). However, the reverse was true for households that were severely food insecure or lived farther from towns. Rwandan and Ethiopian households compared to DRC were less likely to eat CB foods. Policies to stimulate CBE investments in all three countries were largely absent, and quality scientific evidence to guide their development and implementation is currently insufficient.